Chronic nonspecific multiple-sites pain [CNMSP] of unknown etiology: Biopsychosocial method of evaluation for the primary care level - Deepak Goel; Priya R. Avinash; Sushant Shangari; Malini Srivastav; Ashwani Pundeer (Journal of Family Medicine and Primary Care, 2024)
Background: Understanding and dealing with chronic nonspecific pain (CNP) is the important entity at primary care hospital. Chronic nonspecific multiple-site pain [CNMSP] of unknown etiology creates diagnostic and therapeutic challenges for primary care physicians due to lack of guidance regarding evaluation and treatment. Aims and Objectives: To classify and formulate the evaluation, treatment strategies, and prediction of prognosis of patients with CNMSP of unknown etiology. Methods: Patients present with CNMSP of more than 3-month duration without any obvious medical cause. The biopsychosocial [BPS] model with 3P model was applied to see the biological, psychological, and social factors behind persistence. Finally, patients were classified into four groups for evaluation response to treatment and relapse rates in 12-month follow-up. Results: Of the total 243 patients of CNMSP, 243 [96.3%] were females. Sixty [24.7%] patients had short duration, and 183 [75.3%] had long duration. Headache was in 115 [47%], low back pain ± leg pain in 96 [39.4%], cervical pain ± shoulder/arm pain in 83 [34.1%], and diffuse body pain in 50 [20.5%] in various combinations. A total of 155 [63.8%] patients had high somatization–sensitization index (SSI), and 144 [59.3%] had low ferritin level. Group 1 [high SSI and low ferritin] had 37.9% of patients, group 2 [high SSI and normal ferritin] had 25.9% of patients, group 3 [low to medium SSI with low ferritin] had 21.4% of patients, and group 4 [low to medium SSI with normal ferritin] had 14.8% of patients. Response to pain symptoms was better in group 1, and relapse rate was higher in group 2. Conclusion: CNMSP of unknown etiology itself is a heterogeneous entity, and assessment based on the BPS model can be very useful to understand the treatment plan and outcome of these patients.